Cathelicidin‐encoding Lactococcus lactis promotes mucosal repair in murine experimental colitis. Issue 3 (March 2017) - Wong, Clover C M; Zhang, Lin; Wu, William K K; Shen, Jing; Chan, Ruby L Y; Lu, Lan; Hu, Wei; Li, Ming X; Li, Long F; Ren, Shun X; Li, Yi F; Li, Jiang; et al.
Abstract: Background and Aim: The preventive effect of intrarectal administration of mouse cathelicidin (mCRAMP) and oral administration of mCRAMP‐encoding Lactococcus lactis (N4I) has been shown in murine experimental colitis. It is pivotal to understand the ability of N4I whether it can promote mucosal repair in existing colitis. Methods: Mice with dextran sulfate sodium‐induced ulcerative colitis (UC) were treated orally with L. lactis or its transformed strain with or without nisin induction. The body weight, clinical symptoms, and histological changes of colonic tissues were determined. Sulfasalazine was used as a reference drug. Young adult mouse colon cells were used to further elucidate the direct action and possible mechanisms of mCRAMP to promote colonic wound repair. Results: Results showed that N4I could improve the clinical symptoms, maintain crypt integrity and preserve mucus‐secreting layer in colitis animals. The preparation also could prevent cell death and promote cell proliferation. In contrast, effective dose of sulfasalazine only alleviated clinical symptoms but not the mucosal damage and repair in the colon. In vitro study further showed that mCRAMP could directly promote wound repair by accelerating cell migration but not cell proliferation through the GPCR/MAPK pathway. Conclusions: mCRAMP‐encoding L. lactis could be a potential therapeutic preparation better than the traditional anti‐inflammatory agent in the treatment of UC.